Pulse-shape discrimination of the new plastic scintillators in neutron–gamma mixed field using fast digitizer card. (November 2015) - Jančář, A.; Kopecký, Z.; Dressler, J.; Veškrna, M.; Matěj, Z.; Granja, C.; Solar, M.
Abstract: Recently invented plastic scintillator EJ-299-33 enables pulse-shape discrimination (PSD) and thus measurement of neutron and photon spectra in mixed fields. In this work we compare the PSD properties of EJ-299-33 plastic and the well-known NE-213 liquid scintillator in monoenergetic neutron fields generated by the Van de Graaff accelerator using the 3 H(d, n) 4 He reaction. Pulses from the scintillators are processed by a newly developed digital measuring system employing the fast digitizer card. This card contains two AD converters connected to the measuring computer via 10 Gbps optical ethernet. The converters operate with a resolution of 12 bits and have two differential inputs with a sampling frequency 1 GHz. The resulting digital channels with different gains are merged into one composite channel with a higher digital resolution in a wide dynamic range of energies. Neutron signals are fully discriminated from gamma signals. Results are presented. Abstract : Highlights: A newly developed digital spectrometric system employing a fast digitizer card has been verified. The PSD properties of EJ-299-33, BC-501A and BC-501 scintillators are compared by measurements in the Van de Graaff laboratory. All scintillators achieve improved discrimination capability by utilizing the composite digital channel.